Functional properties of La0.99X0.01Nb0.99Al0.01O4−δ and La0.99X0.01Nb0.99Ti0.01O4−δ proton conductors where X is an alkaline earth cation. Issue 4 (April 2015) - Ivanova, Mariya E.; Meulenberg, Wilhelm A.; Palisaitis, Justinas; Sebold, Doris; Solís, Cecilia; Ziegner, Mirko; Serra, Jose M.; Mayer, Joachim; Hänsel, Michael; Guillon, Olivier
Abstract Lanthanum niobates with general formulas of La0.99X0.01Nb0.99Al0.01O4−δ and La0.99X0.01Nb0.99Ti0.01O4−δ (X = Mg, Ca, Sr or Ba) were synthesized via the conventional solid state reaction. Specimens with relative density above 96% were produced after sintering. Structural and phase composition studies revealed predominant monoclinic Fergusonite structure for the majority of samples. SEM and TEM studies elucidated the effect of the used dopant combinations on grain growth, micro-crack formation and secondary phase formation. Results from microstructural study were correlated to the grain interior and grain boundary conductivities for selected samples (La0.99Sr0.01Nb0.99Al0.01O4−δ and La0.99Sr0.01Nb0.99Ti0.01O4−δ). The majority of co-doped niobates exhibited appreciable protonic conductivity under humid atmospheres at intermediate temperatures. Sr- or Ca-doped compounds displayed the highest total conductivities with values for LSNA equal to 6 × 10−4 S/cm and 3 × 10−4 S/cm in wet air and in wet 4% H2–Ar (900 °C), respectively. Additionally, thermal expansion was studied to complete functional characterization of co-doped LaNbO4.